BENTUK CAMPUR KODE DALAM NOVEL MERINDU BAGINDA NABI KARYA HABIBURRAHMAN EL SHIRAZY - Mar’atus Sholiha; Suprani Suprani; Dase Erwin Juansah (Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this research were to describe kinds of code mixing in Merindu Baginda Nabi novel by Habiburrahman El Shirazy.. Data source of this research is Merindu Baginda Nabi novel by Habiburrahman El Shirazy, first edition on 2018. This research was a descriptive qualitative research. Descriptive data obtained through observed and noted. Research data collected was done by using library study technique, observed technique, and noted technique. Data analyze technique used was contextual analysis technique. Data was analyzed by using theory that stated by Suwito. The result of this research showed that code mixing that occurred in Merindu Baginda Nabi novel by Habiburrahman El Shirazy consisted of; (1) code mixing on word forms; (2) code mixing on phrase forms; (3) code mixing on clause forms; (4) code mixing on baster forms; (5) code mixing on repeated word forms; (6) code mixing on idiom forms. Based on analysis result can be concluded that in Merindu Baginda Nabi novel by Habiburrahman El Shirazy existed code mixing in dialogue (character discourse) and writer’s narrative (description) into words, phrases, clauses, basters, word repeat, and idiom.